O significado das escolas rurais multisseriadas no contexto do município de São Gonçalo dos Campos - BA - Lima, Laís Alcântara Rios (2015)
The study about multigrade rural schools based on the rural individuals is justified by the importance of the topic in the social, political and academic scope, since it is important to investigate, to know and to understand the problems of multigrade classes and its social educational peculiarities. Therefore, this research aims to analyze the meaning of multigrade rural schools for the individuals of the school community, in the context of São Gonçalo dos Campos, in the interior of Bahia. Anchored in the discussion about rural education, this study presents a qualitative research using case study. The places of study were two schools in the aforementioned county: an active school and another deactivated. The participants in this research were: one representative of the county educational administration, teachers of the multigrade rural schools and parents of students. The data collection instrument was a semi-structured interview and the data was analyzed based on content analysis. From the data produced, it has been identified that the parents find positive value in schools located the rural communities where they live regardless of pedagogical organization adopted by them. For them the multigrade rural schools are seen as a guarantee to the right to have an education, as spaces that belong to the community history, as responsible for school education and social education of the individual and as a “vehicle” that allows them to have the long awaited “social climbing”. The teachers see the multigrade rural schools as an important local institution because it allows the kids to study where they live, besides the fact that they are a space for the community to socialize and for the families to get together. Both the parents and teachers emphasize the poor conditions of the school infrastructure as a negative aspect, a factor that drives students away rather than attract them. For the county administration, the multigrade rural schools do not promote a learning environment for the students and for that reason they represent more of a problem than a challenge for the public educational work and investments. The study shows that the closing of the multigrade rural schools in the São Gonçalo dos Campos County has proved to be a phenomenon that causes many impacts on the community and routine of the families in the social, symbolic and emotional context. Such phenomenon, justified by the government as a strategy to improve the education in the rural areas of the county, is neither in line with the Rural Education Policy nor with the wishes and opinions of the individuals from the rural communities that participated in this research. The study also shows the need to prepare an educational plan for the São Gonçalo dos Campos County articulated with the debates about Rural Education and in line with the social-cultural demands of the rural individuals.